Sequential Dual Coating with Thermosensitive Polymers for Advanced Fiber Optic Temperature Sensors - Tejaswi Tanaji Salunkhe; Il Tae Kim (Sensors, 2023)
We systematically designed dual polymer Fabry–Perrot interferometer (DPFPI) sensors, which were used to achieve highly sensitive temperature sensors. The designed and fabricated DPFPI has a dual polymer coating layer consisting of thermosensitive poly (methyl methacrylate) (PMMA) and polycarbonate (PC) polymers. Four different DPFPI sensors were developed, in which different coating optical path lengths and the resultant optical properties were generated by the Vernier effect, changing the sequence of the applied polymers and varying the concentration of the coating solutions. The experimental results confirmed that the PC_PMMA_S1 DPFPI sensor delivered a temperature sensitivity of 1238.7 pm °C−1, which was approximately 4.4- and 1.4-fold higher than that of the PMMA and PMMA_PC_S1-coated sensor, respectively. Thus, the results reveal that the coating sequence, the compact thickness of the dual polymer layers, and the resultant optical parameters are accountable for achieving sensors with high sensitivity. In the PC_ PMMA-coated sensor, the PMMA outer layer has comparatively better optical properties than the PC, which might produce synergistic effects that create a large wavelength shift with small temperature deviations. Therefore, it is considered that the extensive results with the PC_PMMA_S1 DPFPI sensor validate the efficacy, repeatability, reliability, quick reaction, feasibility, and precision of the temperature readings.